2011
DOI: 10.1117/12.882955
|View full text |Cite
|
Sign up to set email alerts
|

Critical challenges for EUV resist materials

Abstract: Although Extreme ultraviolet lithography (EUVL) is now well into the commercialization phase, critical challenges remain in the development of EUV resist materials. The major issue for the 22-nm half-pitch node remains simultaneously meeting resolution, line-edge roughness (LER), and sensitivity requirements. Although several materials have met the resolution requirements, LER and sensitivity remain a challenge. As we move beyond the 22-nm node, however, even resolution remains a significant challenge. Chemica… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
41
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 57 publications
(44 citation statements)
references
References 21 publications
3
41
0
Order By: Relevance
“…According to this hypothesis, we have developed a new EUV additive that reform only properties of film surface from hydrophobic to hydrophilic (Scheme 1), and defectivity data of the resist with this new EUV additive is summarized in Figure 9. This clearly shows that adding the new EUV additive to the hydrophobic resist reduced density of blob defect from 100 counts/cm 2 Figure 9. Density of blob type defect for resist (a) without a EUV additive and (b) with a EUV additive.…”
Section: Breakthrough Technology For Improving Tradeoff Between Resolmentioning
confidence: 97%
See 2 more Smart Citations
“…According to this hypothesis, we have developed a new EUV additive that reform only properties of film surface from hydrophobic to hydrophilic (Scheme 1), and defectivity data of the resist with this new EUV additive is summarized in Figure 9. This clearly shows that adding the new EUV additive to the hydrophobic resist reduced density of blob defect from 100 counts/cm 2 Figure 9. Density of blob type defect for resist (a) without a EUV additive and (b) with a EUV additive.…”
Section: Breakthrough Technology For Improving Tradeoff Between Resolmentioning
confidence: 97%
“…We have investigated that resist blur of CAR is comparable with that of non CAR if we utilize PAG with controlled design, especially polymer bound PAG (PBP) [7,8]. Recent studies have been also revealed that CAR enables resolution capability down to 18 nm by decreasing thickness of resist film even though sensitivity is still high, 40 mJ/cm 2 , for satisfying manufacturing requirement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A 21 nm block mask resolution was not affected by exposure dose and explored toward low dose down to 18 mJ/cm 2 by reducing quencher loading. In addition, there was a negligible amount of increase in LCDU for isolated dot pattern when decreasing exposure dose from 66 mJ/cm 2 to 24 mJ/cm 2 . On the other hand, there appeared tradeoff relationship between LCDU and dose for dense dot pattern, indicating photon-shot noise restriction, but strong dependency on patterning features.…”
mentioning
confidence: 95%
“…Dark mask limitation due mainly to mask defectivity issue makes NTI with EUV favorable approach for printing block mask to produce logic circuit. A good resolution of CD-X 21 nm/CD-Y 32 nm was obtained for block mask pattern using NTI with usable process window and dose of 49 mJ/cm 2 . Minimum resolution now reaches CD-X 17 nm / CD-Y 23 nm for the block.…”
mentioning
confidence: 99%